Globalised, Commodified and Privatised: current international trends in education and education policy - Stephen J. Ball (Arizona State University, 2014)
This article analyses some aspects about the privatization of education and of education policy as an international phenomenon of increasing significance. It explores how the world of education is changing and education is changing in the world by looking at the international reach, complexity and dynamism of the education services industry (ESI). It is organized in three sections. The first one addresses some aspects of the new international education economy. Secondly, it looks at some examples of the multiple forms of current educational privatizations (contracting out, Private Finance Initiatives, Public Private Partnerships and "selling" policy) and at the concomitant changes in the form and modalities of the state. Finally, the conclusion establishes some relationships among these aspects.